Should you use artificial insemination and/or embryo transfer in your swine operation? - Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The use of AI and embryo transfer in swine herds will undoubtedly increase during the next decade. The techniques themselves will undergo refinement and improvements as swine producers learn to use them and to manage the genetic aspects of their herds. These techniques should not be viewed as useful tools only for large swine herds. In fact, the relative genetic advantage is probably greater for the medium-sized or small herd, since the superiority of the AI sires compared to boars otherwise available to these herds is relatively greater. Also, access to breeds that are not locally available is an important benefit. The only limitation is the individual producer's desire and abilities, since there is no expensive equipment that will improve results. In fact, AI could become an important equalizer in the distribution of genetic material in the swine industry. In planning for the future, we should also realize that a genetic revolution is just beginning. The Swine Testing and Genetic Evaluation System (STAGES), which is just being implemented by the eight breed associations, will soon make possible comparisons of sires across farms for growth, feed efficiency, and carcass and maternal traits. STAGES will improve the accuracy of selecting superior sires and will provide a means of establishing a national sire listing similar to those presently available in the beef and dairy industries. Estimates of genetic merit will be expressed as predicted progeny deviation (PPD's), which are estimates of how the future progeny of an individual is expected to perform compared to that of an average individual. AI and embryo transfer will be important tools in providing access to the outstanding breeding animals developed with STAGES.
Keywords: Swine; artificial insemination; Embryo transfer